Comparison of Islamic Unit trust performance with conventional - Mohd Yasin, Ahmad Bukhari; Mohamed, Zulkifli; Nafi, Mohd Noor Azam; Kairan, Omar; Ismail, Md Khairu Amin; Ab Rahman, Amri; Othman, Zaihan (Universiti Teknologi MARA, Kelantan, 2018)
Performance of Islamic Unit trust is a very important issue to Muslims as their concern is not just benefits of this life but also for hereafter. This study investigates whether Islamic unit trust able to outperform conventional. There are 46 Islamic and 53 conventional unit trusts products covering five-year performance has been selected in the study. For comparison purposes, there are five performance measurements has been selected, namely; percentage growth, risk/ reward, Sharpe, Treynor and Tracking error. Two Independent samples t test has been employed to assess whether there are differences of mean between Islamic with conventional based on performance measurement respectively. This study found that except for Tracking error, all the performance measurements indicate that conventional unit trusts has outperform Islamic unit trusts significantly.